2023
DOI: 10.3758/s13415-023-01127-y
|View full text |Cite
|
Sign up to set email alerts
|

Two is company: The posterior cerebellum and sequencing for pairs versus individuals during social preference prediction

Naem Haihambo,
Qianying Ma,
Kris Baetens
et al.

Abstract: Previous studies have identified that the posterior cerebellum, which plays a role in processing temporal sequences in social events, is consistently and robustly activated when we predict future action sequences based on personality traits (Haihambo Haihambo et al. Social Cognitive and Affective Neuroscience 17(2), 241–251, 2022) and intentions (Haihambo et al. Cognitive, Affective, and Behavioral Neuroscience 23(2), 323–339, 2023). In the current study, we investigated whether these cerebellar areas are sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Neurological studies have found that cerebellar Crus 1 and 2 were preferentially recruited when we have to memorize sequences of higher-order traits ( Pu et al, 2020 ), beliefs ( Heleven et al, 2019 ; Ma et al, 2021 ) and goal-directed social navigation ( Li et al, 2021 , 2024 ) in comparison to conditions that did not explicitly require sequencing or involved non-social events (cf. meta-analysis by Van Overwalle et al (2020) Importantly, Crus 1, 2 and lobule IX were also preferentially recruited when making predictions about upcoming actions based on known traits ( Haihambo et al, 2022 ), intentions ( Haihambo et al, 2023 ) and preferences of others ( Haihambo et al, 2023 ) in comparison with non-sequential and non-social conditions. Together these studies suggest that the posterior cerebellum plays a key role in sequencing, mentalizing and future oriented thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological studies have found that cerebellar Crus 1 and 2 were preferentially recruited when we have to memorize sequences of higher-order traits ( Pu et al, 2020 ), beliefs ( Heleven et al, 2019 ; Ma et al, 2021 ) and goal-directed social navigation ( Li et al, 2021 , 2024 ) in comparison to conditions that did not explicitly require sequencing or involved non-social events (cf. meta-analysis by Van Overwalle et al (2020) Importantly, Crus 1, 2 and lobule IX were also preferentially recruited when making predictions about upcoming actions based on known traits ( Haihambo et al, 2022 ), intentions ( Haihambo et al, 2023 ) and preferences of others ( Haihambo et al, 2023 ) in comparison with non-sequential and non-social conditions. Together these studies suggest that the posterior cerebellum plays a key role in sequencing, mentalizing and future oriented thinking.…”
Section: Introductionmentioning
confidence: 99%